2019
DOI: 10.1111/ped.13961
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of real‐time continuous glucose monitoring in infants

Abstract: Background: Neonatal hypoglycemia is a common and treatable risk factor for neurological impairment. Real-time continuous glucose monitoring (RT-CGM) can show glucose concentration in real time. Using an RT-CGM alarm, physicians can be alerted and intervene in hypoglycemia. No reports, however, have evaluated the reliability of RT-CGM at low glucose levels in infants. This study therefore investigated the difference between blood glucose (BG) and RT-CGM sensor data at low glucose levels and assessed the optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…MARD is the average of the absolute error between all CGM values and is routinely calculated and reported as a key metric by manufacturers. Despite significant improvements in CGM since first-generation devices 15 , accuracy is still not clinically acceptable at hypoglycaemia values 16,17 and more so in non-diabetic patients: The best published MARD value in neonates at hypoglycaemia is 16% 18 with only 86% of values in Zone A (allowing clinically correct decisions) on a Modified Clarke Error Grid (MCEG) 19 (Figure 2). In the clinical setting these values are suboptimal when compared to manufacturers figures for patients with diabetes 20,21 .…”
Section: Accuracy Of Cgm At Hypoglycaemiamentioning
confidence: 99%
“…MARD is the average of the absolute error between all CGM values and is routinely calculated and reported as a key metric by manufacturers. Despite significant improvements in CGM since first-generation devices 15 , accuracy is still not clinically acceptable at hypoglycaemia values 16,17 and more so in non-diabetic patients: The best published MARD value in neonates at hypoglycaemia is 16% 18 with only 86% of values in Zone A (allowing clinically correct decisions) on a Modified Clarke Error Grid (MCEG) 19 (Figure 2). In the clinical setting these values are suboptimal when compared to manufacturers figures for patients with diabetes 20,21 .…”
Section: Accuracy Of Cgm At Hypoglycaemiamentioning
confidence: 99%
“…In contrast, continuous glucose monitoring (CGM) is an attractive alternative and is widely used by people with type 1 diabetes. The accuracy of CGM in babies with hypoglycaemia remains contentious with unacceptable levels of correlation with standard methods of glucose testing . However, CGM is increasingly improving with evolution of sensor quality and ability to correlate with plasma glucose at the lower end of the glucose range.…”
Section: General Principles Of Hypoglycaemia Correctionmentioning
confidence: 99%
“…Twenty-five of these studies were excluded because they did not meet the eligibility criteria (online supplemental eTable 2). Open access Fifteen articles were included [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] as 14 studies (two records reported on the same population. 34 36 Two of these studies 37 38 had a mixed population consisting of both term and preterm infants.…”
Section: Searchmentioning
confidence: 99%
“…One looked at patients with a mean age of 65 days 29 and one at patients between 5 and 140 days of age. 33 Thresholds most commonly used in included studies were <2.5 and <2.6 mmol/L (range 2.2-2.8 mmol/L) for hypoglycaemia, >10 mmol/L for hyperglycaemia (range 6.7-10 mmol/L). All studies used CGM devices as their index test but calibrated with different frequencies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%